Perancangan Interior Gereja Bethany di Malang - Alition Claudia Angeline Petriana; Mariana Wibowo; Stephanie Melinda Frans (Intra, 2018)
Bethany Church Malang has been established since 2015 and experienced a rapidly growing number of congregations. The need for worship space is increasing, where the congregation that initially only amounted to 100 people developed into 1000 people in every week. Inadequate Interior Design with a standard design and less comfortable is the reason for the need for a new Church design. Therefore, the new church will be built with a unique building form with a seed analogy that will grow and bring impact to the surrounding environment with an area of 2600 m2. Using 7 design methods (accept situation, analyze, define, ideate, select, implimentation, evaluate) and take the concept of Biophilic Design by exploiting the existing natural potential in the environment. This will make the congregation and minister of God feel closer to God and his creation. The results of this design in the form of Worship Space that accommodates 800 people with the facilities for the congregation such as prayer room, counseling room, cafeteria and there are many containers for the congregation can socialize with each other.